Frequency and Clinical Characteristics of Heart Failure with Preserved Ejection Fraction Patients in a Tertiary Level Hospital (University Heart Journal, 2019)
Background: Heart failure with preserved ejection fraction (HFpEF) has already emerged as the predominant form of heart failure in the western world. We aimed to estimate the frequency and clinical characteristics of HFpEF cohort in Bangladesh as limited data are available about this extremely heterogeneous syndrome.Methods: This cross sectional study was conducted at the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka from December, 2017 to December, 2018. A total of 124 heart failure patients were enrolled in the study for the estimation of frequency of HFpEF. Comorbidities and presentation of 30 HFpEF patients were assessed. HFpEF diagnosis was made according to the 2016 European Society of Cardiology (ESC) Guidelines.Results: The frequency of HFpEF was 30 (24.1%) (95% confidence interval 16.6% to 31.7%). The mean (SD) age of was 65.0 (10.1) years. Majority of the patients (73.3 %) were between 60 to 79 years of age. Majority of the patients (60%) were male. Most of the patients had multiple comorbidities and risk factors. Hypertension was the most prevalent risk factor which was present in 80% cases. Dyslipidemia was found in 63.3% cases, DM in 53.3% cases. 36.6% patients had coronary artery disease (CAD). CKD was found in 30% cases. 26.6% patients had atrial fibrillation, which was the most common arrhythmia. 62.0% were overweight to obese. Anemia was found in 55.1% cases. 73.3% patients presented in a decompensated stage of NYHA IV. Breathlessness was the most common (100%) complaint, whereas bilateral lung base crepitations was the most frequent sign (96%).Conclusions: This study findings has paved the way for characterization of HFPEF in Bangladeshi population but more large scale epidemiological studies are needed.University Heart Journal Vol. 15, No. 2, Jul 2019; 63-67